Development of Interactive Multimedia Based on ISpring Suite Integrated Prompting Question to Facilitate Students' Concept Understanding Ability - Dini Aulia Putri; Gusnedi Gusnedi (Department of Physics Universitas Negeri Padang, 2023)
The 21st century has been characterized by great advances in science and technology. These developments have efficiently addressed many issues in the field of education, in the study of physics. Effective physics learning focuses on students' concept understanding. However, the reality is that students' concept understanding is low, especially in the material of traveling waves and stationary waves. The proposed solution is to develop interactive multimedia based on iSpring suite integrated with prompting questions. The purpose of this interactive multimedia is to determine its characteristics and validity. The type of research used is development research using the Plomp development model. Initial data was collected using a four tier diagnostic test and analysis of 2 interactive multimedia journals. The validity test was conducted by 5 lecturers of Physics FMPA UNP. The validity analysis results reached 0.85 valid category.